2020
DOI: 10.1088/1367-2630/abab3d
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical structure factors of a two-dimensional Fermi superfluid within random phase approximation

Abstract: Based on random phase approximation, we numerically calculate dynamical structure factors of a balanced two-dimensional (2D) Fermi superfluid, and discuss their energy, momentum and interaction strength dependence in the 2D BEC–BCS crossover. At a small transferred momentum, a stable Higgs mode is observed in the unitary 2D Fermi superfluid gas where the particle–hole symmetry is not satisfied. Stronger interaction strength will make the visibility of the dispersion of Higgs mode harder to be observed. We also… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 45 publications
2
0
0
Order By: Relevance
“…We note in passing that our result that the peak in Im χ H (ω + iδ, q) in 2D exists for all µ > 0 (in contrast to 3D, where the peak only exists for µ > 0.8267∆), agrees with a previous numerical study, which found that the Higgs mode is more visible in the dynamical structure factor in 2D compared to 3D [45]. We also note that as µ → 0, the boundary frequency ω 2 = 2∆ + q 2 2m µ ∆ approaches 2∆, i.e.…”
Section: Susceptibility χH (ω Q) Along the Real Axissupporting
confidence: 93%
See 1 more Smart Citation
“…We note in passing that our result that the peak in Im χ H (ω + iδ, q) in 2D exists for all µ > 0 (in contrast to 3D, where the peak only exists for µ > 0.8267∆), agrees with a previous numerical study, which found that the Higgs mode is more visible in the dynamical structure factor in 2D compared to 3D [45]. We also note that as µ → 0, the boundary frequency ω 2 = 2∆ + q 2 2m µ ∆ approaches 2∆, i.e.…”
Section: Susceptibility χH (ω Q) Along the Real Axissupporting
confidence: 93%
“…This is consistent with the hidden nature of the Higgs mode. The disappearance of the observable Higgs peak in the BEC regime, where µ < 0, agrees with previous theoretical results in 3D [36,47,48], experimental results for 3D cold-atom systems [33], and numerical studies in 2D [45]. As in the case of positive µ, the ABG mode is visible below the two-particle continuum.…”
Section: E the Higgs Mode For µ supporting
confidence: 90%